2013
DOI: 10.1080/02786826.2012.731094
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Solid Particle Deposition in 90° Ventilated Bends of Rectangular Cross Section with Turbulent Flow

Abstract: Nowadays, ventilation ducts, especially duct bends, play a significant role in filtering aerosol contaminant for the built environment. This article experimentally investigates practical averaged aerosol deposition in 90 • ventilated bends of rectangular cross section by measuring particle concentration changes at bend inlet and outlet in steady state. The measured penetrations at Reynolds number Re = 17,900 and 35,600 are in good agreement with previously published data at small Stokes number, which justifies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…In general, the accurate measurement of particle behavior and deposition in complex turbulent air flows are quite challenging for experiments, while it could be numerically predicted with suitable CFD models [12,13]. For aerosol particle flows, the Eulerian-Lagrangian methods have been proved as effective and credible models to predict particle deposition in turbulent flow by many researches [14e18].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the accurate measurement of particle behavior and deposition in complex turbulent air flows are quite challenging for experiments, while it could be numerically predicted with suitable CFD models [12,13]. For aerosol particle flows, the Eulerian-Lagrangian methods have been proved as effective and credible models to predict particle deposition in turbulent flow by many researches [14e18].…”
Section: Introductionmentioning
confidence: 99%
“…e fluctuating velocities of particle flow were found to be higher than those of airflow at the inlet of the bend. Tables 1 and 2 [10,[14][15][16][17][18][19][20][21][22][23][24]. e scarcity of experimental work during earlier years might be attributed to the reason that both the particle deposition and distribution are comprehensive and can be varied by many factors even in straight pipe/channel/ducts [25][26][27][28].…”
Section: Particle Flow Measurement Through Bendsmentioning
confidence: 99%
“…e aerosol deposition in the bend was found to be larger than that in straight ducts with fully developed turbulent flows. Sun et al designed laboratory experiments to test the particle flow through bends made of different materials in the ventilation system [22,23]. ey discovered particle concentration distribution, deposition, and penetration phenomena and developed models on deposition velocity and penetration.…”
Section: Investigatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu and Li [10] simulated the deposition characteristic of particles at different air velocities for d p = 1-30 lm, and showed that an increase in curvature of the pipe induces a reduction of the particle penetration. Sun et al [11,12] investigated the particle concentration distribution and deposition in three-dimensional 90 degrees bends experimentally, and demonstrated the effects of inlet mass concentration, Reynolds number and wall material on the particle concentration distribution and deposition.…”
Section: Introductionmentioning
confidence: 99%